2013
DOI: 10.7785/tcrtexpress.2013.600268
|View full text |Cite
|
Sign up to set email alerts
|

11C Choline PET Guided Salvage Radiotherapy with Volumetric Modulation Arc Therapy and Hypofractionation for Recurrent Prostate Cancer after HIFU Failure: Preliminary Results of Tolerability and Acute Toxicity

Abstract: The purpose of this work was to evaluate tolerance, feasibility and acute toxicity in patients undergoing salvage radiotherapy after high-intensity focused ultrasound (HIFU) failure. From 2005 to 2011 a total of 15 patients were treated with HIFU as primary radical treatment. Between July 2011 and February 2013, all 15 patients presented biochemical relapse after HIFU and 11C choline PET documenting intrapostatic-only failure. Salvage EBRT was performed with moderate hypofractionation schedule in 28 fractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…HIFU therapy has been used in Japan [ 50 ], but in other countries this therapy has been reported with contradictory results, sometimes failing [ 51 ] and sometimes showing improved results in secondary hyperparathyroidism treatment in patients with chronic kidney disease [ 52 ]. More radical negative results were published this year when all the prostate cancer patients treated with HIFU relapsed after approximately 6 years after HIFU treatment [ 53 ]. The conclusion of the results published until now using HIFU is the need to accumulate more clinical experience in this type of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…HIFU therapy has been used in Japan [ 50 ], but in other countries this therapy has been reported with contradictory results, sometimes failing [ 51 ] and sometimes showing improved results in secondary hyperparathyroidism treatment in patients with chronic kidney disease [ 52 ]. More radical negative results were published this year when all the prostate cancer patients treated with HIFU relapsed after approximately 6 years after HIFU treatment [ 53 ]. The conclusion of the results published until now using HIFU is the need to accumulate more clinical experience in this type of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…reported a range of 3–136 months between HiFU and salvage RT with a median of 39 months. Median time to salvage therapy was also around 30 months in a few other studies, 10–12 while others more consistently showed 12–15 months 13–17 . Importantly, the median PSA values prior to salvage therapies also varied greatly, with a broad range of values reported by certain studies ( e.g .…”
Section: Discussionmentioning
confidence: 91%
“…In this subgroup of patients, PSAdt and PSAvel were significantly higher than those with lymph node or distant metastases. Alongi et al [40] analyzed 15 patients who underwent salvage EBRT due to a biochemical recurrence after high intensity focused ultrasound (HIFU). In these selected patients, 11C-Choline showed a positive intraprostatic-alone failure, thus being able to give information about the target definition in salvage EBRT, although it would still be considered an experimental procedure.…”
Section: Discussionmentioning
confidence: 99%